Analisa Kandungan Bakteri Salmonella sp. pada Telur Ayam dari Pasar Tradisional di Jakarta Selatan - Deanti Raka Siwi; Rina Hidayati Pratiwi; Shafa Noer (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Chicken eggs are a source of protein from animals needed by the human body which contains a lot of complete essential amino acids. Various types of eggs, especially chicken eggs, are foods that are practical to use because they are easy to process and easy to get anywhere. The purpose of this study was to analyze the content of Salmonella sp. bacteria. On chicken eggs sold in the Traditional Market area of South Jakarta. The samples used were 9 samples of chicken eggs taken from Menteng Pulo Market, Sunday Market and West Tebet Market. Based on the results of the research that has been done, it was obtained from 9 chicken egg samples taken from three traditional markets in South Jakarta (Menteng Pulo Market, Sunday Market and West Tebet Market) Salmonella sp. and West Tebet Market, while chicken eggs from Menteng Pulo Market did not contain Salmonella sp. It can be concluded that the quality of chicken eggs from the traditional market in South Jakarta is quite good because out of 9 samples, only 2 samples were contaminated with Salmonella sp.